CORRELATION BETWEEN PRESEPSIN AND SEQUENTIAL [SEPSIS-RELATED] ORGAN FAILURE ASSESSMENT (SOFA) SCORE AS AN ORGAN DYSFUNCTION MARKER IN SEPSIS - Stevi Dwiyani; Agnes Rengga Indrati; Leni Lismayanti; Adhi Kristianto S (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. The latest consensus in 2016 (Sepsis-3) identified organ dysfunction as an acute change in total SOFA score ≥2 points. An ideal laboratory examination is expected to detect sepsis in an early stage and correlated with the degree of infection. Presepsin or Soluble Cluster of Differentiation 14 Sub Type (sCD14-ST) is a proteolysis product of CD14 that is produced in 1-2 hour after innate immune activation during infections. The aim of this study was to determine the correlation of presepsin and SOFA score as an organ dysfunction marker in sepsis. This research was an observational, analytical cross-sectional study conducted in the Dr. Hasan Sadikin Hospital (RSHS) Bandung from September 2016 until July 2017. The subjects were 42 patients from the Emergency Department diagnosed as sepsis by clinicians using criteria of SOFA score ≥2 points. The serum sample was collected and measured for presepsin concentration. A correlation test was analyzed with Spearman analysis. This study showed the increasing of presepsin concentration associated with SOFA score (p=0.000; r=0.660). There was a positive correlation between presepsin and SOFA score as an organ dysfunction marker